Analysis of 2013 Curriculum Character Values in Science Learning - Jumadi Jumadi; Sultini Sultini; Yetti Latifah (Jurnal Penelitian Pendidikan IPA, 2022)
In the world of education only glorify intelligence alone, there will be a crisis of national character values. With changes in the educational curriculum, character values ​​can be instilled in learning in schools. This study aims to describe the character values ​​of students in science learning in pesantren-based schools. In this article, the research researcher applies a qualitative descriptive method by means of observation and interviews. Based on the data obtained in this article, there is a significant change in character values ​​in science learning at the Islamic boarding school-based MTs Nurul Falah. In the 2013 curriculum character values with the Core curriculum (known with KI 1) about spiritual attitudes with religious character values and (KI 2) about social attitudes with seven-character values, namely, honesty, discipline, responsibility, tolerance, courtesy, mutual cooperation and self-confidence. obtain positive changes, so that the cultivation of character values must always be applied in the social attitudes of students